2017
DOI: 10.1177/0013161x17718023
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Departmental Leadership for Professional Learning Communities

Abstract: Purpose: Department heads play a pivotal role in the functioning of departments in secondary schools. However, quantitative research about the role of departmental leadership for the development of professional learning communities (PLCs) in subject departments in secondary schools remains scarce. As PLCs are seen as promising contexts for teachers’ continuous professional development, it is highly relevant to study how department heads can facilitate PLC characteristics in their department. Research methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 49 publications
(119 reference statements)
1
43
1
1
Order By: Relevance
“…The low frequency of interventions directed at team leaders and principals in the current study contrasts the findings of Vanblaere and Devos (2018), who carried out a questionnaire study with 248 teachers from 62 departments of 32 secondary schools. They conclude that departmental leaders who focused on facilitating and stimulating teacher collaboration enhance teachers' feelings of shared responsibility for the quality of teaching and learning in their school.…”
Section: Learning Leadershipcontrasting
confidence: 96%
“…The low frequency of interventions directed at team leaders and principals in the current study contrasts the findings of Vanblaere and Devos (2018), who carried out a questionnaire study with 248 teachers from 62 departments of 32 secondary schools. They conclude that departmental leaders who focused on facilitating and stimulating teacher collaboration enhance teachers' feelings of shared responsibility for the quality of teaching and learning in their school.…”
Section: Learning Leadershipcontrasting
confidence: 96%
“…Hord (1997) proposed that the basic requirements necessary for building PLCs include shared leadership, shared vision, collective learning, peer feedback, and available physical conditions and human capacities. Research has demonstrated that strong leadership support also plays a significant role in making PLCs effective (Fulton & Britton, 2011; Turner et al, 2018; Vanblaere & Devos, 2016, 2018).…”
Section: The Conceptual Basics Of Plcsmentioning
confidence: 99%
“…Tucker described it in 1981 as being "first among equals," meaning in this context that the p chair is occupied by a faculty member (Riley and Russell, 2013). However, this definition is not universally applicable because of its inherent ambiguities and in the varying methods of selecting chairs (Vanblaere and Devos, 2018).…”
Section: Departmental Leadershipmentioning
confidence: 99%
“…The essence of departmental leadership is the ability to build a collective functionality that fulfils the objectives of both department and institution (Gmelch, 2004;Chu, 2006;Vanblaere and Devos, 2018). Accordingly, chairs are tasked with numerous disparate roles and responsibilities.…”
Section: Departmental Leadershipmentioning
confidence: 99%